Glypican‐3: A promising biomarker for hepatocellular carcinoma diagnosis and treatment - Zhou, Fubo; Shang, Wenting; Yu, Xiaoling; Tian, Jie (Medicinal research reviews, 2018)
Liver cancer is the second leading cause of cancer‐related deaths, and hepatocellular carcinoma (HCC) is the most common type. Therefore, molecular targets are urgently required for the early detection of HCC and the development of novel therapeutic approaches. Glypican‐3 (GPC3), an oncofetal proteoglycan anchored to the cell membrane, is normally detected in the fetal liver but not in the healthy adult liver. However, in HCC patients, GPC3 is overexpressed at both the gene and protein levels, and its expression predicts a poor prognosis. Mechanistic studies have revealed that GPC3 functions in HCC progression by binding to molecules such as Wnt signaling proteins and growth factors. Moreover, GPC3 has been used as a target for molecular imaging and therapeutic intervention in HCC. To date, GPC3‐targeted magnetic resonance imaging, positron emission tomography, and near‐infrared imaging have been investigated for early HCC detection, and various immunotherapeutic protocols targeting GPC3 have been developed, including the use of humanized anti‐GPC3 cytotoxic antibodies, treatment with peptide/DNA vaccines, immunotoxin therapies, and genetic therapies. In this review, we summarize the current knowledge regarding the structure, function, and biology of GPC3 with a focus on its clinical potential as a diagnostic molecule and a therapeutic target in HCC immunotherapy.